2022
DOI: 10.3233/mgc-210116
|View full text |Cite
|
Sign up to set email alerts
|

Alginate poly and oligosaccharide (AOS) from Sargassum sp. as immunostimulant in gnotobiotic artemia challenge tests and antibacterial diffusion disc assay against pathogenic Vibrio parahaemolyticus, V. vulnificus and V. harveyi

Abstract: Alginate is a polysaccharide derived from Sargassum sp. and is a potent immunostimulant with antibacterial activity, including against Vibrio spp. This genus of bacteria is found in freshwater and marine environments and is a common infectious, pathogenic bacteria both for aquatic cultivans and humans. Here, we determined the ability of sodium alginate polysaccharides and oligosaccharides (AOS) to act as immunostimulants in Artemia challenge tests and antibacterial diffusion disc assays against Vibrio parahaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…L. bulgaricus in our trial may act similar response in our trials even though the experiments from Talwalkar and Kailasapathy (2003) indicated that different oxygen induction remained unaffected by the metabolic and biochemical changes, including SOD activity. Based on our investigation about bacterial challenges, the application of Artemia as a bio model is well-de ned (Yudiati et al 2021;Yudiati et al 2022). So therefore, the easiness, economically viable, and simple administration, nonselective lter feeder of Artemia (Crustacea) can be valuable information to be adapted for the shrimp culture (Crustacea).…”
Section: Discussionmentioning
confidence: 99%
“…L. bulgaricus in our trial may act similar response in our trials even though the experiments from Talwalkar and Kailasapathy (2003) indicated that different oxygen induction remained unaffected by the metabolic and biochemical changes, including SOD activity. Based on our investigation about bacterial challenges, the application of Artemia as a bio model is well-de ned (Yudiati et al 2021;Yudiati et al 2022). So therefore, the easiness, economically viable, and simple administration, nonselective lter feeder of Artemia (Crustacea) can be valuable information to be adapted for the shrimp culture (Crustacea).…”
Section: Discussionmentioning
confidence: 99%
“…Care should be taken not to pour too little or too much. Then, the solidified media was wrapped and placed in sterilized plastic (Yudiati et al, 2022). 2.4 Antibiotic activity testing on Vibrio sp.…”
Section: Purification Of Vibrio Spp Isolatesmentioning
confidence: 99%
“…As a result, shrimp farming has observed issues related stress-stimulated disease caused by declining pond circumstances prevalence. Our previous study reported that innate immunity is highly related to disease resistance [5], [9]. Furthermore, preventing pathogen aggregation and increasing shrimp resistance to pathogens are the crucial aspects.…”
Section: Introductionmentioning
confidence: 99%